A new anterior approach to parastomal hernia repair (PHR) with linear stapler suture: A case report. (December 2020) - Francesco, Serra; Bonaduce, Isabella; Cabry, Francesca; Sorrentino, Lorena; Iaquinta, Tommaso; Fenocchi, Sara; Roberta, Gelmini
Abstract: Introduction: Parastomal hernia is a type of incisional hernia occurring in abdominal integuments in the vicinity of a stoma. The best surgical approach for PSH remains controversial. Most studies report short follow-up time after surgery and a low number of cases to allow conclusions. Actually, we don't have a relevant recommendation about an optimal surgical technique or the most effective mesh for PSH repair. Presentation of the case: Once packaged the latero-lateral mechanical anastomosis to restore the continuity of the intestinal tract of the patient, an adequate disinfection of trough of the stoma was done. The lateral and medial margins of the defect are then transposed towards each other and kept side by side with a gripper; a 60 mm tristaple linear stapler was placed, incorporating both edges and the charge is fired to obtain a perfect synthesis of the retromuscular plane. Discussion: In the literature has been described several surgical techniques for its repair: suture repair, relocation, mesh-based technique with open or laparoscopic approach. Both, the simple corrective surgery of Thorlakson in 1965 and the use of the peritoneomuscular flap for closing the defect, suggested by Bewes, led to high incidence of recurrence. An important reduction in the rate of parastomal hernia derives also from the mesh reinforcement of the stoma trephine. Conclusion: The authors suggest that this technique should be help the surgeons to repair parastomal hernia in patients with multiple risk factors to develop a recurrence of parastomal hernia. Highlights: The best surgical approach for Parastomal Hernia repair (PSH) remains controversial. Causes that predispose to the development of incisional hernia are multiple, such as obesity and diabetes. This technique may help the surgeons to repair the PSH in patients with risk factors to develop a recurrence after surgery.